MANAGEMENT OF HAEMORRHAGIC SHOCK BY BLOOD TRANSFUSION IN A GRADED MURRAH BUFFALO AFFECTED WITH CERVICO-VAGINAL PROLAPSE - Mani, Selvaraju; Venkatraman, Varudharajan; Mani, Periyannan; Duraisamy, Gopikrishnan; Sreeranjani, Raju; Krishnamurthy, Senthilkumar (Buffalo Bulletin, 2025)
A full term pregnant primiparous graded Murrah buffalo was presented to the Large Animal Obstetrics Unit, VCC and VCRI Namakkal with the history of cervico-vaginal prolapse with profuse bleeding. Animal was cast in the hindquarter elevator and blood vessels of the prolapsed mass were clamped temporarily with artery forceps and further ligated. Cervix was dilated after fanning and feathering and a dead male fetus was delivered by traction by keeping the prolapsed mass outside the vulva. After fetal delivery prolapsed mass was repositioned as per standard procedure. Since the PCV value was less than 15%, blood transfusion was done. Post operatively the animal was treated for five days with antibiotics and the buffalo recovered uneventfully. The present communication reports the significance of blood transfusion for the successful management of prepartum cervico-vaginal prolapse with severe blood loss.